(untitled) (Hoboken, N.J., 2007)
In this book leading profesionals in the semiconductor microelectronics field discuss the future evolution of their profession. The following are some of the questions discussed: Does CMOS technology have a real problem? Do transistors have to be smaller or just better and made of better materials? ....
Keywords: Nanotechnology,Microelectronics,Công nghệ nano,Vi điện tử